Community around the Child: Evaluation of a program to reduce the criminalisation of Australian youth in out-of-home care - Newton, Danielle C (Journal of criminology, 2022)
Young people in residential out-of-home care are universally over-represented in the criminal justice system. This study presents an evaluation of Community around the Child, an early-intervention initiative designed to reduce contact with the criminal justice system among young people living in residential care in Victoria, Australia. Interviews and focus groups with professionals (n?=?44) produced data that were analysed using inductive thematic analysis. The study found the program promoted positive relationships between young people in care and police and between police and residential carers. Increased knowledge on the part of both carers and police about the impact of trauma on young people?s behaviour and methods for supporting young people to regulate their behaviour contributed to these positive relationships. The study calls for a holistic, therapeutic response to the individual needs of young people who have experienced and continue to experience trauma. Essential to this is the provision of training in trauma informed care for police and other stakeholders.